Siloxane-PMMA hybrid anti-corrosion coatings reinforced by lignin - Harb, Samarah Vargas [UNESP]; Cerrutti, Bianca Machado [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Hammer, Peter [UNESP] (Elsevier, 2015)
Novel organic-inorganic hybrid coatings prepared using siloxane-poly(methyl methacrylate) (PMMA) were synthesized using the sol-gel process, with incorporation of lignin to improve mechanical strength, thermal stability and hydrophobicity, while maintaining the high anti-corrosive protection of siloxane-PMMA coatings. Dispersion of lignin in the siloxane-PMMA hybrid was analyzed by optical microscopy. Structural, morphological and wettability analysis of the about 2.5 μm thick coatings, deposited on carbon steel by dip-coating, was performed by X-ray photoelectron spectroscopy, atomic force microscopy and contact angle measurements. Thermal stability was investigated by thermogravimetry and the mechanical properties were studied by microhardness and microscratch measurements. Electrochemical impedance spectroscopy was used to evaluate corrosion resistance in saline aqueous environments. All coatings showed good dispersion of lignin in the hybrid matrix and low surface roughness between 0.3 and 0.4nm. Incorporation of lignin increased hydrophobicity, microhardness and scratch resistance, in addition to shifting thermal degradation events to higher temperatures. The electrochemical tests showed that the hybrids act as efficient diffusion barriers, with corrosion resistance in the range of 108Ωcm2 after exposure to 3.5% NaCl aqueous solution. The hybrid containing a intermediate lignin content of 0.10wt.% presented the best result, exhibiting the most hydrophobic surface (87.9° water drop contact angle), the highest hardness value (31.5 HV), high scratch resistance (up to 80.7mN) and elevated impedance modulus (108Ωcm2) after 50days exposure.
Keywords: Anti-corrosion coatings; Lignin; Siloxane-PMMA hybrid; Sol-gel process